Onychomycosis: Old and New - Narges Maskan Bermudez; Giselle Rodríguez-Tamez; Sofia Perez; Antonella Tosti (Journal of Fungi, 2023)
Onychomycosis is a common chronic fungal infection of the nail that causes discoloration and/or thickening of the nail plate. Oral agents are generally preferred, except in the case of mild toenail infection limited to the distal nail plate. Terbinafine and itraconazole are the only approved oral therapies, and fluconazole is commonly utilized off-label. Cure rates with these therapies are limited, and resistance to terbinafine is starting to develop worldwide. In this review, we aim to review current oral treatment options for onychomycosis, as well as novel oral drugs that may have promising results in the treatment of onychomycosis.